Self-assembly of a barnacle cement protein (MrCP20) into adhesive nanofibrils with concomitant regulation of CaCO₃ polymorphism - Mohanram, Harini (2022)
Barnacles are convenient model organisms to study both biomineralization and bioadhesion phenomena. They secrete a proteinaceous adhesive from cement proteins (CPs) to strongly attach to solid immersed substrates. More recently, it has been suggested that some CPs also play a key role in regulating the calcification of barnacles’ protective shells. In this study, combining both solution and solid-state NMR spectroscopy, Raman and infrared spectroscopy studies, and atomic force microscopy (AFM) and transmission electron microscopy (TEM) imaging, we have explored the CaCO3 mineralization pathway regulated by Megabalanus rosa CP 20 (MrCP20). Our data show that MrCP20 can sequestrate inorganic calcium and carbonate ions from the solution state, which quickly coarsen into liquid-like microdroplets and subsequently form protovaterite amorphous CaCO3 (ACC) particles. This pathway leads to the stabilization of the metastable vaterite polymorphism of CaCO3. Simultaneously, AFM and TEM investigations show that MrCP20 undergoes fibrillization triggered by a pH drift arising during CaCO3 mineralization, leading to amyloid-like nanofibrils. Based on protein NMR, this mechanism appears to be stabilized by the reduction of intramolecular disulfide bonds. Collectively, our results demonstrate that MrCP20 plays a synergistic role of regulating CaCO3 biomineralization while concomitantly self-assembling into adhesive nanofibrils.